Epistemologi Ilmu: Perbandingan Dan Titik Temu Metodologi Ilmu Alam, Ilmu Sosial, Dan Ilmu Agama - Nasrullah, Amin (AZKIYA, 2022)
AbstractionMethodology and approach are fundamental issues in any scientific study.Methodology is an inseparable part of a scientific study that gives consideration tothe validity and truth of science itself. Methodological confusion resulted in thevalue of the validity of the resulting knowledge. The methodology of science is builton the epistemological conception which is the basis for the selection of researchmethods or studies of that science in particular (ad hoc), so that the methodology hasa distinctive style in each discipline. The methodology and approach of a scientificdiscipline are closely related to the epistemic conception of the science. Pure scienceor natural science, which is generated and based on experience and sensing frompurely empirical reality, not the same as the methodology of the religious scienceswhich, apart from being based on observation (intidzar) also involves the heart andintuition. In the scientific tradition which is dominated by positivism from thecurrent natural science paradigm, there are methodological conflicts and crises,which demand new methodologies and approaches. The methodology is built fromparadigmatic assumptions that are accommodative to various disciplines.Methodology and approach that is the meeting point of various disciplines,especially the natural, social, and religious sciences. This requires a review in therealm of epistemology. Epistemology pays special attention to the sources and methodologies used to obtainknowledge systematically. Studying the methodology of science, means discussingissues in the area of epistemology. Epistemologically, the Qur'an mentions that ingeneral there are three sources of knowledge, the universe, humans, and history.Thus, the study of the religious sciences is systematically related to the study of thesocial and natural sciences, which allows the methodology of another discipline tobe used in the methodology of the religious sciences. These are the things that arediscussed in this article. Keywords: positivism, empiricism, intidzar, preconception, naturalistic method,sunnatullah, acquired knowledge, perennial knowledge